Samorządna Rzeczpospolita – 25 lat samorządu w Polsce - Buzek, Jerzy (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2015)
The discussion of the role of self-government in Poland’s political structure has been closely linked to the Polish people’s aspirations and desire for freedom, democracy and a state in which sovereignty is indeed in the hands of its people. These aspirations, so strongly expressed during the general election of June 1989, have since the very beginning included demands for self-government. What it meant for the state and its political system, was the implementation of the idea embodied in the name Solidarity which, as a trade union, was also to be independent and self-governing. It was also the realisation of the demand for a ‘Samorządna Rzeczpospolita’ (a Self-governing Republic), one of the fundamental principles of the Solidarity movement put forward at its First National Congress, which I had the honour of chairing in 1981. In March 1990, only a few months after its election on 4 June 1989, the Polish parliament adopted a law that restored the institution of local self-government at the level of communes and municipalities (gmina). Thus, 25 years ago, the road to political transformation in Poland was opened, allowing the building of a Polish state understood as the political community of all its citizens – a real Res Publica. The predominating belief which accompanied us in this process was that the indispensable prerequisite to shaping democracy was to give back the state to its citizens, thus releasing dormant social energy and the entrepreneurial spirit of the people. After all democracy means not only the possibility of the democratically electing the political representatives (the authorities) but equally the chance for citizens to feel involved and take the responsibility for public affairs. Therefore the first democratic government, headed by Tadeusz Mazowiecki, began the process of restoring the state to its citizens from the most important starting point. It started with the rebuilding of communal and municipal self-governing structures and the recreating of the intellectual foundations for the formation of the new constitution of a citizens-centred state. This was possible mainly because a vision of reform had already been conceived and had been long developing in the minds of a number of distinguished persons. This project of self-government reform constituted an original example of engagement of Polish intellectuals in state affairs and their taking responsibility for the common good. The reform also turned out to be one of the most effective methods of de-communisation of Polish public life. This could be best seen in the results of the first election to self-governing structures in 1990, and the role which the Solidarity citizens’ committees played in it. It was indeed the same people, the co-founders and members of the Solidarity movement, who have successfully carried out the restoration of self-government in Poland. ‘We marched for power to return it to the people’ was the motto of the Polish government in 1997, a government which I had the honour of heading for the subsequent four years, and which articulated the goals and the sense of political and social transformation of those times. We called it a Four Reform Programme, and its objective was a fundamental transformation of public life in Poland. On the one hand we intended to create favourable conditions for the development of the public civic space, while on the other we strove to activate and make more dynamic the processes of economic, political and cultural development in the country. We believed that acceleration of this development and modernisation was contingent upon active participation of self-government structures. Hence the creation of strong self-government had gradually become our conscious choice and an urgent ‘civilising task.’ This task was grounded equally in the need to manage properly our recently regained independence, and in the need to make efficient use of the pre-accession period preceding Poland’s membership of the European Union, which was then imminent. Thus the administrative reform undertaken by my government in 1999 introduced districts (powiat) as self-governing level of administration, allowing it, in conjunction with communes and municipalities (gmina), to take effective control of matters directly affecting local communities and their citizens. The self-governing structures formed at the level of strong voivodships, or regions, allowed at the same time to decentralise responsibility for regional economic development, competitiveness and modernisation strategies. Today, after over 10 years of EU membership, it is worth reflecting on the impact the political reforms which we carried through then have had on Poland’s functioning in the system of European integration. We were proven right in our conviction that decentralisation and differentiation of various state functions would allow for a better and more effective use and management of EU funds. The three-tier self-government structure created solid foundations helping to satisfy better the aspirations of citizens, local communities and regions with regard to their modernisation and development. Today it is those local self-governing units, those closest to citizens, those most familiar with and with the best understanding of their needs, which are responsible for the drafting of regional development projects and the management of funds available for those projects. Self-government structures have become the real centres for formulating and implementing development strategies. This is the context in which the key challenge facing self-government is set, namely the fostering of entrepreneurship, ensuring proper conditions for innovation and mobilising citizens to engage in economic and social initiatives. The role of self-government in shaping of the state’s development policy is not limited to dividing available means and resources. Much more important is its ability to effectively multiply the available means, to support partnership ventures, including public-private projects, to form strong business to business relationships as well as partner relations between research centres and local administrative bodies, or promote and support innovations and civic initiatives serving the common good. After all, all these are key factors for the long-term stability and development of our communities and our country, which is today the key measure of the responsibility for public matters, so deeply rooted in the idea of self-government. The self-government reform originated from the ideas developed in the 1980s of the twentieth century as part of the Solidarity movement, but was implemented in an already independent Poland, when laying the foundations for a transformation of the state and the democratisation of the citizen-state relationship. It also had, however, and maybe predominantly, a deep idealistic dimension, so easy to forget when we focus on the current and most urgent challenges of the present. In my opinion, it is in self-governance, as well as in the political and administrative culture, that opportunities for building our freedom lie: freedom, the sense of which we feel best if given a chance to share in the responsibility for it. In times of independence this means the possibility of personal engagement public issues based on the pro publico bono principle: issues pertaining to our family life, our local community, or the whole country. Today, in the context of our shared responsibility for the European Union, such an understanding of self-governance should also inspire us to seek new directions of development, and to participate in the shaping of Europe-wide standards of public life. In the same way as 25 years ago in Poland we founded a political community on the basis of self-governance, we should today look at self-governance as a chance to create a true political community of all European citizens.